Prevalence and Factors Associated with Hypertension in the Coastal Com-munity of Laha Village: A Cross-Sectional Study - Etrin Zulqarnain Eka Saputra Linggar; Irwan; Melda Yunita; Ivanmorl Ruspanah; Augie Desvie Klausya Kadun; Fadila Tri Starlia; Maxwell Landri Vers Malakauseya; Noviyanter Siahaya (Nusantara Science and Technology Proceedings, 2023)
High blood pressure, often known as hypertension, is a worldwide health issue linked to a higher risk of cardiovascular illnesses. Targeted strategies for the prevention and management of hypertension will benefit from an understanding of the prevalence and risk factors for hypertension in particular groups. The purpose of this study was to ascertain the prevalence of hypertension in the coastal community of Laha Village, Ambon City, and to pinpoint the contributing factors. The information came from a 2022 health survey that was carried out in Laha Village's coastline homes. We made use of data gathered from 757 respondents. In this study, concomitant diseases, lifestyle, and demographic status were the independent variables, and hypertension was the dependent variable. The method of multivariate logistic regression was employed for data analysis. We discovered that 6.4% of the residents of Laha Village's coastline community had hypertension. Demographic variables were significantly associated with hypertension, especially in the age ranges of over 60 (aOR=28.18; 95% CI:3.27-242.97; p=0.002) and 41–60 years (aOR=10.09; 95% CI:1.20-84.47; p=0.033). The results showed an interesting correlation between non-smoking (aOR=12.50; 95%CI: 1.54-101.13; p=0.018) and occasional smoking (aOR=13.95; 95%CI: 1.42-136.35; p=0.023) and hypertension. Additionally, a strong correlation was discovered between hypertension and concomitant joint illnesses (aOR=3.03; 95% CI: 1.60-5.70; p <0.001). Our findings imply the need for promoting a healthy lifestyle to reduce the risk of hypertension, particularly among coastal communities. This includes encouraging the adoption of a healthy diet and increased physical activity. Furthermore, our study emphasizes how critical it is to create and carry out community-wide awareness initiatives in Laha Village. The coastal population should be educated about hypertension through these efforts, with a focus on the importance of early detection, routine blood pressure monitoring, and lifestyle adjustments for both management and prevention.